Compassion Fatigue among Physicians and Nurses Working in the Intensive and Critical Care Units of Hospitals in Ulaanbaatar, Mongolia - Bazarragchaa, Sodnom; Purevdorj, Tseden; Turbat, Battsetseg; Enkhdalai, Delgermaa; Lkhagva, Bayarmagnai; Luvsan, Munkh-Erdene (Central Asian Journal of Medical Sciences, 2018)
Objectives: The purpose of this study was to investigate the current state of the burnout and secondary traumatic stress among physicians and nurses in units of hospitals in Ulaanbaatar, Mongolia. Methods: We used a validated questionnaire of the ProQOL-5 Scale to assess the compassion fatigue of physicians (n=58) and nurses (n=139) who worked in critical and intensive care, neurosurgery, internal, burn, and palliative care units. We used a descriptive analysis to estimate the correlation between burn out and secondary traumatic stress scores across demographic categories. Results: A total of 197 study participants were recruited in our study. There were 78.7% of all participants had a higher risk of developing burn out and 82.2% of all participants had a higher risk of developing secondary traumatic stress respectively. High levels of burn out were identified among physicians compared with nurses (20.7% vs. 25.9%) respectively, with physicians having a higher prevalence of secondary traumatic stress than nurses by 5.8% . The increased prevalence of secondary traumatic stress was significantly correlated with the number of patients cared for per day (r=0.207, p<0.01) and the unit in which the care provider worked (r=0.163, p<0.01) by the univariate and bivariate analyses. Conclusion: Participants with higher prevalence of burn out and secondary traumatic stress work in high stress units and cared for more patients per day. Physicians had a higher prevalence of burn out that nurses.